Economic burden of symptomatic iron deficiency - a survey among Swiss women - Patricia R. Blank; Yuki Tomonaga; Thomas D. Szucs; Matthias Schwenkglenks (BMC, 2019)
Abstract Background Symptomatic iron deficiency (ID) is a disorder affecting 10-20% of menstruating women. ID is diagnosed by measuring serum ferritin, a protein helping to store iron in the body. A deeper understanding of the association between ID and its societal and economic burden is relevant for patients, physicians, health care decision makers. Methods An online household survey was carried out among Swiss women aged 18-50 years suffering from debilitating symptoms due to ID. The data was population-weighted for age and region. The costs of misdiagnosis and the ID-related economic burden (i.e. days of sick leave) from productivity losses on the labor market were determined and extrapolated to the Swiss population. Furthermore, the patient burden was assessed based on quality of life daily measurements. Results The total sample included 1010 women who received an ID diagnosis with a blood test in the last 2 years (mean age: 33.5 years). Most named symptoms were "being tired or exhausted" (96.4%) and reduced physical energy level (41.0%). In total, 354 (35.0% of the total sample) patients received an initial diagnosis other than ID. Of those, 46.8% were treated prior to the ID diagnosis with a pharmacological medical therapy or psychotherapy. Extrapolating these numbers to the Swiss female population aged 18-50 years, the direct medical costs would be CHF 78 million (assuming an annual ID incidence of ID diagnosis of 9.5%). On average, 28.5% of participants in the work-force had to take sick leave due to ID symptoms within a period of 2 years (mean: 5.2 days, i.e. 2.6 days/year). The estimated annual indirect costs in Switzerland would be CHF 33 million (human capital approach) or CHF 26 million (friction cost method), respectively. Being exhausted and impaired concentration appear to be the most important factors negatively impacting daily living and hence quality of life. Conclusion The societal and economic burden among women due to debilitating symptoms of ID in Switzerland is substantial. Timely, correct diagnosis and treatment of ID may contribute to reducing this burden. Further studies are needed in this area to validate our results.